Performance Requirements for Climate Resilience of Residential Roofs - Shyti, Flonja (Université d'Ottawa / University of Ottawa, 2021)
The roof is one of the most important elements of the building envelope. It offers protection for the homeowners against weather elements. According to the Institute for Catastrophic Loss Reduction (ICLR) houses are less engineered and are much more prone to damages during weather events. Recent climatic changes have increased the severity of weather events and roof failures. This demands the necessity of updating the design, evaluation, and construction methods for asphalt shingle roofs with a holistic approach. A disconnect exists between the service life of a roof and the advertised warranties of asphalt shingles by the manufactures. This is misleading and prevents homeowners from making informed decisions about their roof selection. This thesis reviewed not only the roof's performance in the field but also the current practices followed for the design, evaluation, and construction methods. The review respectively concluded that the current design is based on only historical data, both components and systems are mostly evaluated under lab conditions, rather than being exposed to the weather conditions experienced during the service life, and lack of installation quality assurance. The objective of this thesis is to develop the initial framework for a “Holistic Approach” that would increase the resilience of residential roofs. This has been accomplished in three folds: 1. Quantified the changes in the design wind loads, using both the current and projected changes in wind pressures due to global warming magnitude. Data provided by Environment and Climate Change Canada was used for this analysis and a new web design tool “Climate-RCI” for climate severity classification of cities across Canada was created. 2. Performed an extensive experimental evaluation of components and systems, following established methods and procedures, to quantify the effect of weathering on the resistance of asphalt shingles and roof mock-ups. To achieve this both components and systems were evaluated. For the component, the resistance after being aged in the field for a minimum of 13 years displayed a maximum decrease of 59%. Measured properties of the majority of the aged components no longer met the minimum requirements outlined in the respective standards referenced in the National Building Code of Canada. The system resistance was significantly reduced due to weather exposure. 3. Developed quality assurance guidelines based on best practices in consultation with the roofing industry for various climatic severities. This thesis identified three major future research areas, namely, calibration of an appropriate resistance factor for residential roofs, correlating lab verse field weather exposure conditions, and probabilistic determination of the installation process.
Keywords: Residential Roof; Climate Resilience